Design and production of dies for micro wire drawing - Tan, Guo Dong. (2010)
Wire drawing is the most commonly used process to produce wires for electrical circuit. While the production of wires has improved tremendously in terms of speed and efficiency, the size of wires produced has been neglected. Large scale machines are often used to produce wires of micro level. Such a method is not economical in a mass production industry.